Phenotypes, endotypes and biomarkers in anaphylaxis: current insights. Issue 5 (October 2018) - Sala-Cunill, Anna; Guilarte, Mar; Cardona, Victoria
Abstract : Purpose of review: The aim of the review is to describe the different clinical pictures of anaphylaxis (phenotypes), in relation to the underlying mechanisms and potential biomarkers, to describe anaphylaxis endotypes. This may aid in achieving a better understanding, management and outcomes of such severe reactions. Recent findings: Different anaphylaxis phenotypes have been outlined, ranging from the classical type-I-like to those suggestive of cytokine-storm-like or complement-mediated reactions. Underlying mechanisms differ and biomarkers of cells and systems involved are being identified (tryptase, IL-6, bradykinin etc.) Summary: Identifying specific phenotypes/endotypes will allow the application of precision medicine in patients with anaphylaxis, providing insights to the most appropriate approach in each case.